(untitled) (Journal of Academic Finance, 2013)
In this paper, we are interested in the impact of CSR and social reporting on consumer behavior and thus on the value creation. To enrich the literature and to better understand how CSR reputation can create value for the company, we empirically study the effect of social reporting on the ROS (Return on sales), the variation of turnover and Profit margin through the study of "responsible" behavior of consumers in France. Results show that there is a positive but not significant relationship between social reporting and the change in turnover and profit margins. But there was a significantly positive impact of non-financial disclosure on the return on sales.